The Dybbuk Speaks with the Mouth of the Living: Wartime Trauma and Strategies of Holocaust Remembrance in Hungarian Literature Between 1949 and 1953: Wojenna trauma a strategie pamięci o Zagładzie w literaturze węgierskiej w latach 1949-1953. Próba zarysu - Piotrowiak-Junkiert, Kinga (Porównania, 2023)
The article deals with the subject of the Holocaust in Hungarian literature between 1949 and 1953, and in particular with the writing strategies used by the authors to describe a phenomenon that was silenced and removed from public debate. During the post-war period, when the Communists were in power in Hungary, it was forbidden to write about the war and especially about the Holocaust of the Jews; moreover, all literary texts had to be approved by the censors. Despite the strict restrictions, Hungarian writers managed to smuggle the forbidden topic into their novels. In this article, I discuss the prose of József Debreczeni, István Kamjén, and Ferenc Karinthy against the background of social and historical phenomena in Hungary.